2011
DOI: 10.1143/jjap.50.05eb01
|View full text |Cite
|
Sign up to set email alerts
|

Isobutyl Silane Precursors for SiCH Low-k Cap Layer beyond the 22 nm Node: Analysis of Film Structure for Compatibility of Lower k-value and High Barrier Properties

Abstract: To form SiCH films with a high carbon content using plasma-enhanced chemical vapor deposition (CVD), isobutyl trimethylsilane (iBTMS) and diisobutyl dimethylsilane (DiBDMS) were examined as precursors for a low-k cap layer and Cu diffusion barrier at the top of Cu lines. We elucidated the relationship between the structure of low-k SiCH films made from these newly developed precursors and their barrier properties against copper and oxygen diffusion. We also studied the relationship between the structure of SiC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Newly designed organic silanes, iBTMS, DiBDMS, SSN and DVScP, were confirmed to be favorable for forming SiCH with a high C content. The high C content in SiCH films prepared using iBTMS or DiBDMS was thought to be derived from the iso-butyl fragment, as reported previously [15]. …”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Newly designed organic silanes, iBTMS, DiBDMS, SSN and DVScP, were confirmed to be favorable for forming SiCH with a high C content. The high C content in SiCH films prepared using iBTMS or DiBDMS was thought to be derived from the iso-butyl fragment, as reported previously [15]. …”
Section: Resultssupporting
confidence: 54%
“…Therefore, we developed precursors iBTMS and DiBDMS for a Si–CH 2 –Si network and C-rich SiCH films [14, 15], and SSN and DVScP for a Si–C 2 H 4 –Si network and C-rich SiCH films [14, 16]. These precursors were designed based on their reactions in plasma estimated by quantum-chemical calculations.…”
Section: Materials Design and Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…[402][403][404][405] Shimizu's results using precursors such as 1,1-divinyl silacyclopentane (DVScP) and 5-silaspiro- [4,4]-nonane (SSN) have shown that a-SiC:H films with a significant improvement in mass density can be achieved for a given dielectric constant relative to a-SiC:H films deposited using traditional tetramethylsilane (4MS) precursors. 403 Using similar precursors, 100 nm a-SiC:H films with k values as low as 3.1 that show Cu diffusion barrier performance equivalent to higher k = 5.0 a-SiCN:H have also been demonstrated. 402,404 Matsuda has also shown that similar a-SiC:H films can exhibit increased fracture strength due to increased crack tip plasticity arising from the more ductile -(CH 2 ) x -bonding.…”
Section: Future Trends and Research Needed For Low-k Db And Es Materialsmentioning
confidence: 99%
“…Carbon and hydrogen rich SiCN films with relatively low dielectric constants (k ≈ 3.5-4) have been considered and reported as promising candidates. 16 In addition, materials with relatively high k values (k ≈ 8-9) such as AlN have been proposed because they can provide good barrier properties at relatively low thicknesses. The selection of cap layers is also an important issue to reduce Cu electromigration.…”
mentioning
confidence: 99%